Estratégias de (re)existência das comunidades quilombolas da Resina e do Saramém, em Brejo Grande/SE - Almeida, Gênisson Lima de (2024)
Traditional peoples and communities are culturally differentiated groups that recognize themselves as such, according to Decree no. 6.040 of February 7, 2007. This decree states that existing traditional groups are diverse and broad. For the purposes of this study, given this diversification, artisanal fishermen and shellfish gatherers were chosen as the object of study. The social subjects carry out their activities through contact with nature, in the territory in which they are inserted, through the direct connection with the waters along the river courses, lagoons and mangroves, which represent the potential of the spatial area. This condition favors the extractive economic activities of artisanal fishing, rice cultivation and shellfish gathering, respectively, in addition to the communities developing Community-Based Tourism (CBT). Each activity therefore reveals the specific characteristics of each individual and/or social group. In turn, quilombola communities have their identity, culture and traditional knowledge as the basis for their existence and affirmation in the territory as quilombolas. The aim of this research was to analyze the (re)existence strategies of the quilombola communities of Resina and Saramém, in Brejo Grande/SE. Among the methodological procedures, the following stand out: a bibliographic survey, based on consultations in the Brazilian Digital Library of Thesis and Dissertation Data (BDTD) of the different HEIs in the PRODEMA Network, Google Scholar and CAPES journals, from the Web of Science collection databases, with an emphasis on scientific articles published in the last five years; a documentary survey, based on the legal instruments that protect quilombola communities and those that guide environmental conservation policy; and a cartographic survey, with the making of a map of the location of the spatial section. The primary data was obtained through field research, using semi-structured interviews, photographic records, social cartography and on-site visits. The ethnomaps generated in the two communities through social cartography made it possible to identify the places used for extractive practices, socio-environmental vulnerabilities and the actions of external forces in the quilombola territory. In addition, the forms of representation of identity, culture and traditional knowledge were explained. The results showed that in artisanal fishing and shellfish gathering, family members are involved in specific roles. Marketing, one of the main stages in the fishing and shellfish-gathering production chain in terms of trade, was predominantly marked by the active presence of middlemen, although they are also quilombolas and fishermen. In quilombola territory, conflicts are triggered by the individual interests of each social subject. To this end, we identified that among the existing conflicts in the area, a new conflict arose involving a multinational oil and gas company and artisanal fishermen and, on the other hand, conflicts between fishermen and farmers increased after the publication of Ordinance No. 234, of November 14, 2023, which recognized quilombola lands and between the artisanal fishermen themselves. The conclusion is that existing public policies need to be effective, i.e. they need to assist artisanal fishermen and shellfish gatherers in order to secure them in the territory and thus encourage extractive practices, corroborating strategies for (re)existence through the traditional knowledge, identity and cultures of these peoples.